Exploring the Longitudinal Relationship between Self-Compassion and Body Dissatisfaction in Female Adolescents: A Prospective Study - Arif Fathansyah; Brechan Nazhan (PELNUS | Pen en Light for Natural Union of Science, 2024)
This study investigates the relationship between self-compassion and body dissatisfaction in female adolescents, aiming to contribute to our understanding of factors influencing adolescent body image and psychological well-being. A longitudinal correlational design was employed to assess self-compassion and body dissatisfaction in a sample of female adolescents. Participants completed validated self-report measures assessing self-compassion and body dissatisfaction at baseline and follow-up assessments spaced several months apart. Data were analyzed using correlational, regression, and longitudinal analyses to explore the association between self-compassion and body dissatisfaction over time, as well as potential moderators and mediators of this relationship. Findings revealed a significant negative association between self-compassion and body dissatisfaction at baseline, suggesting that adolescents with higher levels of self-compassion tend to experience lower levels of body dissatisfaction. Moderation and mediation analyses suggested that factors such as age, social support, self-esteem, and body appreciation may influence the strength and mechanisms of the self-compassion-body dissatisfaction relationship. These findings have important implications for theory, research, and practice, highlighting the significance of self-compassion in promoting positive body image and psychological resilience among adolescent girls.